Effect of Giving Compost on Some Physical Properties of Entisol and the Growth of Corn (Zea mays L) - Chusnul Agustina (Contributions of Central Research Institute for Agriculture, 2022)
This study aims to 1) compare the effect of applying rice straw compost and campus waste compost on several soil physical properties. 2) Comparing the effect of compost dosing on several soil physical properties. 3) Knowing the effect of rice straw compost and campus waste compost on the growth of corn plants. The hypotheses of this study are 1) Applying campus waste compost will have a better effect than rice straw compost in improving some soil physical properties. 2) Applying the highest dose of compost will have a better effect on improving some of the physical properties of the soil. 3) The provision of rice straw compost and campus waste compost can improve the growth of corn plants in Entisols. Entisols are soils that have a sand or loamy sand texture, so they have low water holding capacity and very low organic matter. One way to overcome the low nutrient content in the soil is by adding organic matter in the form of compost.